Optimizing Fishermen's Administrative Completeness through Vessel Measurement Outreach to Improve the Welfare of Coastal Communities in Arowi Village - Filep Wamafma; Nurjannah Lahangatubun; Marwiah’tul Adawiyah Rumkel; Anthon H. Rumbruren; Andi Elrika Natsir (Abdi Masyarakat, 2026)
Arowi Village in Manokwari Regency possesses abundant marine resource potential; however, the welfare of its fishermen remains hindered by administrative constraints and limited access to government assistance. Most traditional fishermen in this region do not yet possess legal vessel documents, which serve as the primary prerequisite for accessing fuel subsidies, insurance, and infrastructure assistance. This Community Service Program (PKM) aims to raise legal awareness and provide technical assistance through vessel measurement outreach for the issuance of Small Pas (E-Pas Kecil) certification. The method employed is a participatory approach involving face-to-face outreach, interactive discussions, and on-site vessel measurement demonstrations conducted by the team from the Class IV Manokwari Harbor Master and Port Authority Office (KSOP). The results show a significant increase in fishermen's understanding of the urgency of vessel legality in accordance with Law Number 17 of 2008 concerning Shipping. Of the 42 fishermen in attendance, 25 vessel units were successfully measured and had their administrative documents processed for the issuance of E-Pas Kecil. The outcomes of this service program provide legal certainty for fishermen, ensure shipping safety, and open accessibility to various sustainable coastal economic empowerment programs.